Assessment of Extraction Methods Effects on the Biological Activities (Antioxidant and Antiamylase) and Chemistry (Total Phenolics and Flavonoids) of Guazuma ulmifolia Leaves - Nuri; endah, puspitasari; bawon, triatmoko; dewi, dianasari; siti, muslichah; arisatia, nugraha (Jordan Journal of Pharmaceutical Sciences, 2024)
The antioxidant activity was tested using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging method. Antiamylase activity was evaluated through a colorimetric assay that employs 3,5-dinitro salicylic acid (DNSA) as a substrate. Total phenolics and flavonoids content were quantified by the colorimetric method. The highest yield from the extraction of G. ulmifolia leaves was obtained from the water extract (9.64%). The infusion showed the most robust antioxidant and antiamylase activities (IC50 = 6.853 ± 0.504 µg/mL and 261.03 ± 6.83 µg/mL, respectively). The highest total phenolics and flavonoids content were found in the ethanolic extract, with 69.848 ± 1.871 mg GAE/g extract and 118.854 ± 1.001 mg QE/g extract respectively. Total phenolics and flavonoids content significantly influenced the antioxidant activity, but not the antiamylase activity. In conclusion, infusions were the best extraction method for obtaining high antiamylase activity, even though they did not yield the highest total phenolics and flavonoids content. Further research is needed to identify the compound in G. ulmifolia leaf infusions that contribute to antioxidant and antiamylase activities.